Difference Level Of Energy, Macronutrients Intake, and Physical Activity In Obese and Non Obese Students in At-Taqwa Islamic Elementary School Wiyung Surabaya - Vivi Ade Rifani,; Ruhana, Amalia (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Background: Obesity is a nutritional problem as a consequense of an imbalance between energy intake and energy expenditure. Factors that may trigger obesity include food intake and daily physical activity. Purpose: To determine the differences in energy intake, macronutrients, and physical activity levels in obese and non obese students. Methods: This study is a quantitative study with a comparative method and a case-control design. The study took place in at SDIT AT-TAQWA Wiyung Surabaya in January 2025. The respondents consisted of 36 obese students and 36 non obese students selected with a purposive sampling technique. Measurement of energy and macronutrient intake levels using a 24-hour recall form instrument with an interview method while physical activity data collected using a Physical Activity Questionnaire for Children (PAQC). Result: Analysis showed that the levels of energy intake (p = 0.000), carbohydrates (p = 0.000), protein (p = 0.000), fat (0.000) and physical activity (p = 0.000). Conclusion: There were differences in of energy intake, macronutrients, and physical activity level in obese and non obese students.